Menopause-Related Symptoms and Influencing Factors in Mosuo, Yi, and Han Middle-Aged Women in China - Wang, Jinyi; Lin, Yezhe; Gao, Limin; Li, Xingjun; He, Chunhua; Ran, Maosheng; Zhao, Xudong (Frontiers in Psychology, 2022)
Although previous studies showed that women’s menopause-related symptoms varied in different ethnic groups and countries and were affected by specific social and cultural factors, few studies have been conducted to explore the menopause-related symptoms and its influencing factors in middle-aged women among ethnic groups in China. This study aimed to explore the characteristics of menopaused-related symptoms and its influencing factors among Mosuo, Yi, and Han women in Yongning area of Yunnan province, China. A cross-cultural design by snowball sampling method was used to recruit 208 women aged 40-60 from Yongning Township, Ninglang County, Yunnan province, China. The 11-item Menopause Rating Scale (MRS) was used to assess the menopause-related symptoms. Compared with Yi and Han women, Mosuo women had the highest family status in family. Multiple linear regression analyses showed that ethnicity, age, family support, and family decision-making pattern were associated with the severity of menopause-related symptoms. Yi and Han women had more severe menopause-related symptoms than Mosuo women. Among the three groups, women living in “female-dominated” and “co-deliberated” households had significantly lower scores of menopause-ralatd symptoms than those in “male-dominated” households. This study indicates that the menopause-related symptoms varies among middle-aged women in different ethnic groups. Higher level of female status in family and family support may be protective factors of menopause-related symptoms in middle-aged women.